THE EFFECTIVENESS OF â€œNEURO-COGNITIVEâ€ LEARNING STRATEGY FOR INCREASING SPEAKING PERFORMANCE: STUDY ON NON-ENGLISH DEPARTMENT STUDENTS - Pratiwi, Widya Rizky; Suardi, Suardi; Acvfira, Lukytta Gusti (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
English is the unifying international language of world communication. However, English-speaking countries face many problems in their position as a foreign language, so learning strategies and motivation must be emphasized in the learning process. On the other side, communication skills are the most needed skills to prepare for the world of work. Thus, this research with a qualitative method approach is focused on investigating the effectiveness of teaching and training on